Novel two-dimensional KAB (A = Cu, Au, B = S, Se) photoelectric materials with Prominent carrier mobility and optical properties. (January 2021) - Ding, Li-Juan; Li, Gui-Gui; Zhang, Chang-Wen; Li, Ping; Wang, Pei-Ji
Abstract: Recently, two-dimensional (2D) semiconducting materials with appropriate direct band gaps have attracted considerable attention, due to their great potential application in photoelectric devices. In this study, by using first-principles calculations we propose new PbFCl-type ternary structures of single layers (SLs) and double layers (DLs), namely KAB (A = Cu, Au and B = S, Se). The results indicate that SLs and DLs of KAB are direct band gap semiconductors, ranging from 0.5 eV to 1.4 eV. More importantly, electron mobilities of KCuS, KAuS and KCuSe are larger than 10 4 cm 2 V −1 s −1, and the superiority of optical absorption during visible light region reveals a potential application prospect in photoelectric devices. These findings provide alternative candidates for the application in photoelectric materials and are conductive to understanding the intrinsic properties and potentials of new-type 2D materials. Highlights: New PbFCl-type ternary structures of KAB (A = Cu, Au, B = S, Se) are proposed. A direct band gap semiconductor characteristic, indicating the easier electron transition. The considerable electron mobility that is comparable to black phosphorene. Efficient optical absorption endow these films with promising application potential in photoelectric.